PROYEKSI KECUKUPAN BERAS DI KALIMANTAN BARAT TAHUN 2020 - B01108096, OKTAVIUS REGEN (Jurnal Pembangunan dan Pemerataan, 2015)
The title of this research is â€œProyeksi Kecukupan Beras Di Kalimantan Barat Tahun 2020â€. The methods used are quantitative methods those as: (1).Using a linear trend forecasting methods, (2).Quadratic trend forecasting methods and (3).Exponential trend forecasting methods. While to calculate the growth of the population used the geometric growth method. The purpose of this study that is: (1).projecting the level rice sufficiency level in West Kalimantan up to 2020 by using time series forecasting method, (2).Choosing the best method to project the level of sufficiency of rice in West Kalimantan until 2020 that will come. From the forecasting methods the time series which used, forecasting methods thatÂ Â  has a value of mean square error is smallest is the quadratic trend forecasting method with forecasting error value that is equal to 746,080,371.35. The results showed that (1).TheÂ  production rice forecasting results of using this quadratic trend of West Kalimantan Province until the year 2020 is estimated to produce as many as 925 767 tonnes of rice, (2).While the projected amount of rice demand in western borneo in 2020 is estimated at many as 719.764 tonnes, (3).West Kalimantan Province in 2020 is estimated to have a surplus of rice as much as 206.003 tonnes. This illustrates that the West borneo Province to will be able to meet its rice sufficiency by 2020 that will come. Keyword : Projection, rice sufficiency